“Wing leaders” in recovery residences: staff key approaches supporting criminal legal system-involved residents receiving medication for opioid use disorder - Dewey, Jodie M.; Tompkins, James; Mericle, Amy; Watson, Dennis P. (Frontiers in Public Health, 2025)
IntroductionRecovery homes (also known as recovery residences or sober living homes) are an effective approach to addressing substance use disorder in the United States and have been classified into four levels of care by the National Association of Recovery Residences (NARR). These homes may be particularly successful in supporting recovery and reintegration for individuals in the criminal legal system (CLS) through increased stability and better employment outcomes, reduced recidivism, and bolstered confidence in remaining substance-free. Despite promising findings, more research across the different recovery residence levels is needed to identify the key elements that contribute to their success. This paper focuses on essential factors identified by staff working at residences which fit within NARR Level 3 for effectively supporting CLS individuals receiving medication for opioid use disorder (MOUD).MethodsAs part of a larger qualitative project of recovery homes most aligned with NARR Level 3, focus groups were conducted with 19 staff members in Chicago-area recovery homes (n = 4) that serve CLS residents receiving MOUD. MAXQDA software was used to organize and analyze data.ResultsAs described by staff, effective support for CLS-involved residents receiving MOUD centers on two recovery goals: (1) promoting sobriety and (2) fostering personal and social stability. To encourage sobriety, recovery home staff address essential needs such as medical care, mental health support, and acquiring identity documents. These homes also waive monthly fees or what most home operators call sustainability fees (room and board). Staff also enforce strict rules and ensure active engagement with program expectations. To support personal and social stability, program content is delivered by staff with significant lived experience in both CLS and substance use.DiscussionThrough programming, staff provide skills-based education to guide residents toward gradual independence aimed at destigmatizing CLS-involved residents and assisting in reintegration. However, the effectiveness of this support may be limited for those receiving MOUD as staff in this study did not actively encourage discussions about MOUD in recovery. This omission potentially reinforces stigma and hinders authentic relationships required for the social model of recovery.